Empowering women in household waste management to overcome the waste crisis in Maro Sebo Village, Jambi - H. Heriberta; Jaya Kusuma Edy; Al Parok; Ovie Yanti; Sri Ningsih (Universitas Muhammadiyah Malang, 2025)
Women often bear the primary responsibility for managing household waste, facing challenges due to inadequate waste policies, limited facilities, and economic dependence. To address these issues, a community engagement program in Maro Sebo Village, Jambi Luar Kota District, Muaro Jambi Regency, was implemented to to provide mentoring for women in household waste management. The program aims to empower women as agents of change in promoting sustainable waste practices through improved awareness and technical skills in recycling, material reuse, and simple technologies aligned with circular economy principles. Additionally, it focuses on developing sustainable business models that allow women to generate income while reducing household waste. Expected outcomes include the formation of a women-led waste cooperative, increased recycling rates, and reduced waste sent to final disposal sites. Ultimately, this initiative seeks to create a replicable model for other communities, contributing to environmental sustainability and local economic empowerment.